Understanding the Heterogeneity of International Students' Experiences: A Case Study of Chinese International Students in U.S. Universities. (November 2019) - Heng, Tang T.
Scholars have critiqued the current understanding of international students for glossing over its diversity, resulting in the reification of the "international student experience" as either homogeneous or clustered along nationality. Through a qualitative case study of 18 Chinese international students, this article examines the heterogeneity of their experiences despite a common nationality. Findings reveal that Chinese international students' communication in English, engagement with subject content, preparation for the future, and participation in extracurricular activities vary by year of study, field of study, and, to a small extent, gender. Even within a single nationality, experiences of students are uneven and intersect across various categorical lines, suggesting the possibility that other international students may encounter diverse and intersectional experiences as well. Findings point to how we need to re-conceive and research international students by examining the heterogeneous nature of their experiences, and how higher education institutions can differentiate support given to internationals.